Geochemistry of the Precambrian Basement of the Bamenda massif of southeastern Nigeria: petrogenesis and tectonic setting - C.U. Ibe (Geologica Acta, 2020)
Trace and Rare-Earth element geochemical study of twenty samples of migmatitic banded gneisses, garnet biotite schists, dolerites, granites and rhyolites was carried out in a bid to determine their petrogenetic and tectonic significance in the evolution of the southeastern Basement complex of Nigeria. The data shows that partial melting (crustal anatexis) of migmatitic gneisses and schists played a significant role in the evolution of the granitic intrusions. This is supported by the high incompatible (Rb/Sr = 0.16 to 1.31 and Ba/Sr = 0.75 to 6.21) elements ratio in the granitic intrusions than that of the migmatitic gneisses and schists (Rb/Sr, 0.051 to 0.824; Ba/Sr, 0.7 to 5). High ratios of Ba/Sr and Rb/Sr and lesser values of Ba/Rb ratios in some granitic intrusions than in others suggests increasing fractionation during the anatexis. The role of partial melting is also evident in the smooth REE patterns shown by most of these rocks and the negative Eu anomaly as indicated by the values of Eu/Eu* (0.097 to 0.7). LREE enrichment is evident in the high values of Ce/YbN (12.08-174.5), La/YbN (15.2-228.4) and La/SmN (2.6-7.2) in the granitic intrusions. Tectonic discrimination diagrams of the rocks indicate that the basement rocks were most probably formed in a post-collision orogenic setting while the dolerite and the rhyolite were formed in within-plate anorogenic setting.